ChemInform Abstract: Novel One‐Pot Synthesis of Symmetrically Substituted Ureas. Issue 52 (6th December 2016) - Wu, Xingxing; Niu, Qingfen; Li, Tianduo
Abstract: The simple and environmentally friendly protocol proceeds with inexpensive reagents.